Sports practice is related to parasympathetic activity in adolescents - Cayres, Suziane Ungari [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Rodrigues, Aristides Machado; Silva, Manuel João Coelho e; Codogno, Jamile Sanches [UNESP]; Barbosa, Maurício Fregonesi; Fernandes, Rômulo Araújo [UNESP] (Elsevier B. V., 2015)
Objective: To analyze the relationship among sports practice, physical education class, habitual physical activity and cardiovascular risk in adolescents. Methods: Cross-sectional study with 120 schoolchildren (mean: 11.7±0.7 years old), with no regular use of medicines. Sports practice and physical education classes were assessed through face-to-face interview, while habitual physical activity was assessed by pedometers. Bodyweight, height and height-cephalic trunk were used to estimate maturation. The following variables were measured: body fatness, blood pressure, resting heart rate, blood flow velocity, intima-media thickness (carotid and femoral) and heart rate variability (mean between consecutive heartbeats and statistical index in the time domain that show the autonomic parasympathetic nervous system activity root-mean by the square of differences between adjacent normal R-R intervals in a time interval). Statistical treatment used Spearman correlation adjusted by sex, ethnicity, age, body fatness and maturation. Results: Independently of potential confounders, sports practice was positively related to autonomic parasympathetic nervous system activity (b=0.039 [0.01; 0.76]). On the other hand, the relationship between sport practice and mean between consecutive heartbeats (b=0,031 [–0.01; 0.07]) was significantly mediated by biological maturation. Conclusions: Sport practice was related to higher heart rate variability at rest.

Objetivo: Analisar a relação entre prática esportiva, educação física escolar, atividade física habitual e indicadores cardiovasculares de risco em adolescentes. Métodos: Estudo transversal que selecionou 120 escolares (idade média 11,7±0,7 anos), sem consumo de medicamentos. Prática esportiva fora do ambiente escolar e educação física escolar foram avaliadas por entrevista face a face, enquanto a atividade física habitual foi avaliada por pedometria. Peso corporal, estatura e altura troncocefálica foram usados para estimar a maturação biológica. Foram avaliados: gordura corporal, pressão arterial, frequência cardíaca durante o repouso, velocidade do fluxo sanguíneo, espessura mediointimal das artérias (carótida e femoral), variabilidade da frequência cardíaca (média entre batimentos cardíacos consecutivos e o índice estatístico no domínio do tempo que representa atividade do sistema nervoso autônomo parassimpático por meio da raiz quadrada da média das diferenças sucessivas ao quadrado entre intervalos R-R consecutivos). Correlação de Spearman verificou relação entre as variáveis. Relacionamentos significativos foram ajustados por: sexo, etnia, idade, gordura corporal e maturação biológica. Resultados: Prática esportiva, independentemente dos ajustes, apresentou correlação positiva com atividade do sistema nervoso autônomo parassimpático (=0,039 [0,01; 0,76]). Por outro lado, a relação entre tal engajamento e a média entre os intervalos R-R (=0,031 [---0,01; 0,07]) foi mediada pela maturação biológica. Conclusões: A prática esportiva foi relacionada a uma maior variabilidade da frequência cardíaca durante o repouso.
Prática esportiva está relacionada à atividade parassimpática em adolescentes
Keywords: Adolescent; Adolescente; Autonomic nervous system; Carotid intima‐media thickness; Espessura mediointimal carotídea; Frequência cardíaca; Heart rate; Prática esportiva; Sistema nervoso autônomo; Sports practice; Frequência cardíaca; Sistema nervoso autônomo; Espessura mediointimal carotídea; Adolescente; Prática esportiva